Evolution of consumer perceptions and intentions in the green cosmetics market: a thematic and trend analysis - Dwivedi, Swati; Gupta, Ashulekha; Sayal, Anu (Frontiers in Sustainability, 2025)
This study examines the evolving research landscape on consumer perceptions and intentions toward green cosmetics, highlighting significant trends and thematic developments. Additionally, it also emphasizes the need to use digital space to amplify the consumers' awareness level. Guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, this review combines synthesizes bibliometric analysis and systematic review, highlighting selected research studies by discussing the moderating variables that may affect purchase intent for green cosmetics. A favorable attitude toward green cosmetics is, however, accompanied by a large “green purchasing gap” whereby green purchasing intentions do not necessarily translate to actual purchases. Thematic cluster further underscores the critical role of psychological and behavioral factors, such as attitudes toward sustainability and perceived product quality, in influencing purchase intentions. This review uncovers key thematic trends of consumer perceptions and intentions toward green cosmetics. It fills a gap by pointing to a persistent “green purchasing gap” and that people's psychological and behavioral factors make a palpable difference in purchase behavior. This analysis distinctively associates the bibliometric and systematic lenses to clarify the persistent “green purchasing gap” using both macro trends and behavioral constructs.